2016
DOI: 10.1111/clr.12841
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy comparison of guided surgery for dental implants according to the tissue of support: a systematic review and meta‐analysis

Abstract: It can be concluded that the tissue of the guide support influences the accuracy of computer-aided implant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(180 citation statements)
references
References 48 publications
6
154
1
4
Order By: Relevance
“…The corresponding figures with bone support were 1.3, 1.56, and 1.7 mm and 1.28 and 1.84 mm, respectively, hence favoring tooth support. The corresponding mean deviations at the apical level were for tooth support 1.01, 1.3, and 1.62 mm and 0.6 and 1.81 mm, respectively, and for bone support 1.6, 1.86, and 1.99 mm and 1.57 and 2.26 mm, respectively, also favoring tooth support 88 …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The corresponding figures with bone support were 1.3, 1.56, and 1.7 mm and 1.28 and 1.84 mm, respectively, hence favoring tooth support. The corresponding mean deviations at the apical level were for tooth support 1.01, 1.3, and 1.62 mm and 0.6 and 1.81 mm, respectively, and for bone support 1.6, 1.86, and 1.99 mm and 1.57 and 2.26 mm, respectively, also favoring tooth support 88 …”
Section: Resultsmentioning
confidence: 90%
“…With tooth support, the angle deviations were reported as 3.39°, 3.5°, and 4.4° in the three prospective studies and 2.91° and 4.88°, in the two retrospective studies included in the meta‐analysis. The corresponding figures with bone support were 4.73°, 5°, and 5.1°; and 4.63° and 9.31°, respectively, hence favoring tooth support 88 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that the use of a surgical guide reduces inaccuracies in the transfer of Clin Implant Dent Relat Res. [9][10][11][12] Other factors influencing accuracy were the type of edentulous space, 13 the nature of the remaining teeth, 14,15 the implant system used, 16 and the surgical approach (flap vs flapless 17 or delayed vs immediate placement 18 ). [1][2][3][4] The individual steps of the planning process must be as precise as possible for the sum of the errors to ultimately yield a clinically tolerable discrepancy between the actual and planned implant positions.…”
Section: B Ac Kgr Oundmentioning
confidence: 99%
“…The literature reports conflicting results regarding the relationship between the type of guide support and the accuracy of postoperative implant position, in relation to the preoperative virtual planning. A previous systematic review (Schneider, Marquardt, Zwahlen, & Jung, ) reported that surgical accuracy is not necessarily related to the type of guide support, while other publications (Pozzi, Polizzi, & Moy, ; Raico Gallardo et al, ; Tahmaseb, Wismeijer, Coucke, & Derksen, ; Van Assche et al, ) found that tooth‐supported guides delivered more accurate results than mucosa‐ or bone‐supported guides. Furthermore, some reported that within the category of tooth‐supported guides, scenarios with single‐tooth gaps showed the most accurate results (Pozzi et al, ).…”
Section: Introductionmentioning
confidence: 97%